Efikasi Kendiri dari Perspektif Teori Sosial Kognitif dan Pendekatan Akhlak dalam Pembangunan Keusahawanan - Wan Yusof, W. N. H. S.; Zainol, F. A. (Universiti Sains Islam Malaysia, 2024)
Psychological theories of entrepreneurship has been a subject of academic interest for more than two decades. However, it is still considered as an emerging field of academic research. Some scholars attribute this to the lack of common agreement of what psychological entrepreneurship is. The study of the factors that leads people to become entrepreneurs has been a question of many researchers. The purpose of this paper is to examine the comparison between existing literature on Social Cognitive Theory and Imam al-Ghazali approach in the development of student itentions to become entrepreneurs. The study can provide feedback to the managerial organization in order to improve the entrepreneurship education which can increase the level of entrepreneurial intention among students of Higher Education Institution (HEI) in Malaysia. This paper was concluded with a discussion on theoretical and practical implications, and suggestions for future research.